THE SIGNIFICANCE OF LITERARY CHARACTERS IN THE WORKS OF CHARLES DIKCENS - Qodirova Shaxlo Qobiljon qizi; Bahodir Aliqulovich Kholiqov (TADQIQOTLAR, 2025)
Abstract This article explores the significance of literary characters in the works of Charles Dickens. Through an analysis of novels such as Oliver Twist, David Copperfield, Great Expectations, and Hard Times, the study demonstrates how Dickens employs characters not only to develop his plots but also to critique the moral, social, and psychological aspects of Victorian society. The article argues that Dickens’ mastery of character development is one of the key reasons his novels remain impactful and relevant today.